THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE, COMPETENCE ON THE PERFORMANCE OF CIVIL SERVANTS (PNS) OF PUBLIC HEALTH CENTER BATU AJI BATAM - Habibi, Habibi; Indrayani, Indrayani; Khaddafi, Muammar; Yanita, Yanita; Mulyadi, Mulyadi (RADJA PUBLIKA, 2022)
The purpose of this research was to determine the causality of the relationship between leadership, organizational culture, competence on the performance of civil servants at Batu Aji Batam Public Health Center. This study uses quantitative methods with analysis tools for the Statistical Package for the Social Sciences (SPSS) 25. The number of research respondents was 42 samples using a questionnaire. The results showed that (1) leadership had no significant effect on the performance of civil servants at Batu Aji Batam Public Health Center; (2) organizational culture has a significant effect on the performance of civil servants at Batu Aji Batam Public Health Center; (3) competence has a significant effect on the performance of civil servants in Batu Aji Batam Public Health Center; (4) leadership, organizational culture, competence simultaneously have a significant effect on the performance of civil servants at Public Health Center Batu Aji Batam